Ocean acidification impacts on Sea Surface biology and biogeochemistry in Northwest European Shelf Seas: a high-replicated shipboard approach. - Richier, Sophie; Achterberg, Eric P; Archer, Steve; Bretherton, Laura; Brown, Ian; Clark, Darren; Dumousseaud, Cynthia; Holland, Ross J; Hopkins, Frances E; MacGilchrist, Graeme A; Moore, C Mark; Poulton, Alex; et al. (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
The goal of this study was to quantitatively investigate the links between changes in the ocean carbonate system and organism physiology and morphometry (including CaCO3 shells), biogeochemical rates, plankton biodiversity and community structure, food webs and climate-relevant processes. For that purpose we devised and implemented a series of highly replicated (n=8), short term (2-4 days) multi-level (>=4 conditions) carbonate chemistry (E1-E5)/nutrient manipulation (E2b, E3b and E5b) experiments on a range of natural microbial communities sampled in the surface mixed layer (<20 m) of Northwest European shelf seas. The cruise was conducted at a time of year with enhanced biological productivity and coccolithophore abundance (June/July 2011; PSO Achterberg). The cruise covered areas of different pH, seasonally stratified and perennially mixed seas, areas of coccolithophore abundance and absence, and areas (e.g. eastern North Sea, influence of Baltic inflow) where low alkalinity decouples CaCO3 from sea surface temperature. The experiments were performed within a purpose-built experimental laboratory container allowing acute temperature and light control. The temperature in the container was set up to match the in situ at the time of the water collection. The light (100 µE m-2 s-1) was provided by LED panels and followed a 16/8 h L/D cycle. In order to provide enough water to measure the multiples variables in triplicate, 9 bottles were dedicated to each time point. A total of 72 bottles were used for each bioassay. The additional bioassays (E2b, E4b and E5b) were run in triplicates for 2 days with a unique sampling point at the end of the incubation. This study provided up to 39 variables measured in each main bioassay. This work constitutes a UK contribution that complements existing/planned international OA research. To our knowledge this study represents the first attempt to link pelagic ocean carbonate system variations with sea-surface biology, biogeochemical rates and climate processes in such a comprehensive manner. Up to 18 scientists from 4 UK institutions (University of Southampton, University of Essex, PML and UCL) were involved in this team effort as part of the Sea Surface Consortium of the UK Ocean Acidification Research Program (UKOA).